2017
DOI: 10.1063/1.4985416
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of fish larvae in mangroves with different root types in Labuhan coastal area, Sepulu – Madura

Abstract: Reducing the level of leaves damage of (Brassica rapa) caused by armyworm (Spodoptera litura F.) through liquid bioinsecticide formulation of bintaro (Cerbera odollam) Abstract.Mangrove root complexity and shading are well known to give positive correlation for both juveniles and adult fishes. However, it is remain unclear whether that complexity would affect the community of fish larvae (ichthyoplankton). This study aimed to address the question, especially in mangrove area in coastal area of Sepulu, Madura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…species richness, density, and biomass were observed at the vegetated area, followed by the pneumatophore area and mudflat at the Sonneratia site. The results indicated that the spatial variations of fish assemblages were highly correlated with mangrove structural complexity; however, the effects of vegetation structural complexity on fish are site-specific, and the general hypothesis of higher structural complexity habitats support higher fish diversity (Muzaki et al 2017) was not supported. In addition, the effects of vegetation structural complexity on fish also varied seasonally.…”
Section: Differences Of Microhabitat Use By Fish In the Mangrove Wetlmentioning
confidence: 75%
“…species richness, density, and biomass were observed at the vegetated area, followed by the pneumatophore area and mudflat at the Sonneratia site. The results indicated that the spatial variations of fish assemblages were highly correlated with mangrove structural complexity; however, the effects of vegetation structural complexity on fish are site-specific, and the general hypothesis of higher structural complexity habitats support higher fish diversity (Muzaki et al 2017) was not supported. In addition, the effects of vegetation structural complexity on fish also varied seasonally.…”
Section: Differences Of Microhabitat Use By Fish In the Mangrove Wetlmentioning
confidence: 75%
“…The net was towed subsurface in proximity of mangroves. The towing path was 100-meter-long and duplicate samples were obtained from each location (Muzaki et al 2017). Collected plankton samples were immediately preserved in 10% buffered-formaldehyde for further analysis in the laboratory.…”
Section: Specimen Collection and Processingmentioning
confidence: 99%
“…Turbidity in all sampling locations was higher than quality standard for marine organism (Ministry of Environment of Republic of Indonesia 2004). However, turbidity in estuary is usually high and can still be tolerated by many larval, juvenile and adult fish (Jorgensen et al 2013;Muzaki et al 2017). Higher turbidity in the estuary could be contributed to by decomposition of mangrove litter which releases tannins into the water (Setiawan 2013), wave action (Lamb et al 2008), higher productivity and sediment inflow due to erosion from land.…”
Section: Environmental Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of thermal adaptation may be important to tropical species living within narrow thermal ranges (Munday et al 2017). Coupled with losses of habitat complexity and ecosystem services, the continued loss of mangrove forests (Duke et al 2007, Teutli-Hernández & Herrera-Silveira 2018 may see dramatic declines of terrestrial fauna (Rog et al 2016) and fish (Muzaki et al 2017) leading to declines of future fauna biomass for mangroves and adjacent fisheries. The loss of species and populations driven by a warming climate is a global concern (Wiens 2016).…”
Section: Introductionmentioning
confidence: 99%